TLRs-JNK/ NF-κB Pathway Underlies the Protective Effect of the Sulfide Salt Against Liver Toxicity - Abdel-latif, Rania; Heeba, Gehan Hussein; Hassanin, Soha Osama; Waz, Shaimaa; Amin, Amr (Frontiers in Pharmacology, 2022)
Hydrogen sulfide (H2S) is an endogenously gas transmitter signaling molecule with known antioxidant, anti-inflammatory, and cytoprotective properties. Although accumulating evidence shows the therapeutic potential of H2S in various hepatic diseases, its role in cyclophosphamide (CP)-induced hepatotoxicity remains elusive. The present study was undertaken to investigate the impact of endogenous and exogenous H2S on toll-like receptors (TLRs)-mediated inflammatory response and apoptosis in CP-induced hepatotoxicity. Either an H2S donor (NaHS (100 μM/kg) or an H2S blocker (dl-propargylglycine (PAG) (30 mg/kg, i.p.)), was administered for 10 days before a single ip injection of CP (200 mg/kg). NaHS attenuated conferred hepatoprotection against CP-induced toxicity, significantly decreasing serum hepatic function tests and improving hepatic histopathology. Additionally, NaHS-treated rats exhibited antioxidant activity in liver tissues compared with the CP group. The upregulated hepatic levels of TLR2/4 and their downstream signaling molecules including c-Jun N-terminal kinase (JNK) and nuclear factor-kappa B (NF-κB) were also suppressed by NaHS protective treatment. NaHS showed anti-inflammatory and antiapoptotic effects, reducing hepatic level tumor necrosis factor-alpha (TNF-α) and caspase-3 expression. Interestingly, the cytotoxic events induced in CP-treated rats were not significantly altered upon the blocking of endogenous H2S. Taken together, the present study suggested that exogenously applied H2S rather than the endogenously generated H2S, displayed a hepatoprotective effect against CP-induced hepatotoxicity that might be mediated by TLRs-JNK/NF-κB pathways.